FIG ENDOPHYTIC BACTERIA PRODUCE ENZYMES AMYLASE, LIPASE, PROOTEASE, CELLULASE - Habsari, Lilis; Gultom, Endang Sulistyarini; Nasution, Mhd Yusuf; Rangkuti, Marlinda Nilan Sari; Pulungan, Ahmad Shafwan S (JBIO: jurnal biosains (the journal of biosciences), 2023)
The use of enzymes in Indonesia is increasing every year, so action is needed to harmonize the production and needs of enzymes in Indonesia. Enzymes can be produced from various sources such as plants, animals and microorganisms. The advantage of utilizing microorganisms in enzyme production is that they can be produced in large quantities with a shorter time and can be produced continuously. One of the sources of bacterial screening to produce enzymes is figs. This study aims to look at the extracellular enzyme activity of fig endophytic bacteria and identify endophytic bacteria capable of producing extracellular enzymes such as proteases, amylase, cellulase and lipase. Isolation and purification of bacteria using NA media for 24 hours. Test of extracellular enzyme activity using NA media enriched with amylum, tween 80, skim milk, CMC. Biochemical tests are performed to identify endophytic bacteria of figs producing extracellular enzymes. The results of the study were 21 isolates of fig endophytic bacteria, as many as 14 isolates were able to produce extracellular enzymes. The identification results of fig endophytic bacteria producing extracellular enzymes obtained 8 isolates suspected to be from the genus Bacillus, 3 isolates suspected to be from the genus Micrococcus, 1 isolate suspected to be from the genus Cellulomonas, 2 isolates suspected to be from the genus Acetobacter